Village Institutions in Sustainable Village Development - Widyawati Widyawati; Yuyun Anggraini (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The establishment of a sustainable village development policy in 2020 has changed the role of village development to become a pillar of sustainable national development. The success of implementing sustainable development in villages is the hope of the government to accelerate the achievement of sustainable development goals at the national level. The key to success in changing the development order in the village lies in adaptive village institutions. This research aims to describe and analyze existing village institutions in Jeneponto Regency in carrying out sustainable village development, using qualitative methods. Sources of research data come from informant information, results of document reviews and various articles related to the research topic. Each data obtained was triangulated and analyzed before being presented in narrative and table form. From the research that has been done, it is known that village institutions in implementing sustainable village development still have deficiencies. Existing formal policies are not in line with the concept of sustainable village development, which shows benefits and reduces the impact of development. Development activities in the development plan have not supported the achievement of sustainable village development. The organizational structure is not directly proportional to the burden of achieving sustainable Village development goals, there is still a lack of human resource capacity, and village partnerships do not create sustainable benefits in improving the village economy